2021
DOI: 10.1115/1.4051147
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dislocation-Mediated Hydrogen Transport and Trapping in Face-Centered Cubic Metals

Abstract: The diffusion of hydrogen in metals is of interest due to the deleterious influence of hydrogen on material ductility and fracture resistance. It is becoming increasingly clear that hydrogen transport couples significantly with dislocation activity. In this work, we employ a coupled diffusion-crystal plasticity model to incorporate hydrogen transport associated with dislocation sweeping and pipe diffusion in addition to standard lattice diffusion. Moreover, we consider generation of vacancies via plastic defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…[ 46,47 ] The movement of the dislocations transports weakly trapped hydrogen and lattice hydrogen toward the regions with high stress concentration, such as grain boundaries, crack tips, and second‐phase interfaces. [ 48,49 ] Wang et al [ 24 ] reported the increased peak hydrogen concentration with decreasing crosshead speed. Meanwhile, Hashimoto et al [ 50 ] found a linear positive correlation between the engineering strain and hydrogen trap density.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46,47 ] The movement of the dislocations transports weakly trapped hydrogen and lattice hydrogen toward the regions with high stress concentration, such as grain boundaries, crack tips, and second‐phase interfaces. [ 48,49 ] Wang et al [ 24 ] reported the increased peak hydrogen concentration with decreasing crosshead speed. Meanwhile, Hashimoto et al [ 50 ] found a linear positive correlation between the engineering strain and hydrogen trap density.…”
Section: Discussionmentioning
confidence: 99%
“…As the relationship between H and plasticity becomes more intricate, dislocation-based plasticity models, particularly those using a crystal plasticity approach coupled with H kinetics, are being explored. 799,800 These models account for vacancy generation and dislocation-mediated H transport, moving toward a more comprehensive simulation of H-accelerated FCG.…”
Section: Effect Of Crystallographicmentioning
confidence: 99%
“…Crystal plasticity approaches could be the key to understand these processes. 799 A possible mechanism that is not commonly addressed but requires further understanding is H pipe diffusion along dislocation cores, which has been proved by DFT calculations for some metals. However, the process was regarded secondary in iron 848 or at a macroscopic level.…”
Section: Knowledge Needs For Determining H Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was applied to the simulation of hydrogen repartition ahead a crack tip in small scale yielding with isotropic elastoplastic material, as in previous works [10,11,31], they showed through a parametric study the effect of the hydrogen transport by dislocation both for bcc and fcc materials, which permits to improve the simulation of hydrogen transport. This approach has been extended to crystal plasticity scale [32,33] to add the influence of polycrystalline texture on the overall hydrogen transport.…”
Section: Introductionmentioning
confidence: 99%